1991
DOI: 10.1001/jama.1991.03470170090030
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Tardive Dyskinesia Incidence in the Elderly

Abstract: The incidence of neuroleptic-induced dyskinesia was 31% (95% confidence interval, 20%, 42%) after 43 weeks of cumulative neuroleptic treatment. Psychiatric (as opposed to organic) diagnosis and presence of extrapyramidal signs early in treatment were associated with increased tardive dyskinesia vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 24 publications
1
47
2
1
Order By: Relevance
“…It is believed that, because these drugs produce fewer EPS, they will be associated with a much lower risk of developing tardive dyskinesia. Preliminary data support this theory (Saltz et al 1991;Casey 1989), but more extensive data are required for definitive conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 98%
“…It is believed that, because these drugs produce fewer EPS, they will be associated with a much lower risk of developing tardive dyskinesia. Preliminary data support this theory (Saltz et al 1991;Casey 1989), but more extensive data are required for definitive conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 98%
“…Saltz et al (1991) reported an incidence of neuroleptic-induced tardive dyskinesia that was six times higher than usual (31% after only 43 weeks of cumulative treatment) in a naturalistic study of 160 patients over the age of 55 (mean age 77 years).…”
Section: Epidemiologymentioning
confidence: 98%
“…Some studies have reported that incidence rates of TD were not related to gender (Saltz et al, 1991). Woerner et al (1991) found that among younger patients men had higher rates of TD, while among patients age 40 and older, the rates were higher in women.…”
Section: Tardive Dyskinesiamentioning
confidence: 99%
“…Incidence rates for new cases of tardive dyskinesia average 5% per year of conventional antipsychotic drug exposure for young patients ( Jeste et al, 1995). In two prospective studies of elderly patients treated with conventional neuroleptic medications for the first time, incidence rate rates of tardive dyskinesia ranged from 20-31% after one year (Jeste et al, 1995;Saltz et al, 1991). Thus, the risk of developing tardive dyskinesia is four to five times higher among elderly patients compared to younger patients for conventional antipsychotic medications.…”
Section: Tardive Dyskinesiamentioning
confidence: 99%